Dual-Band Microstrip Antenna Based on Polarization Conversion Metasurface Structure - Yao, Huiming; Liu, Xinyi; Zhu, Hongbo; Li, Haihong; Dong, Guoyan; Bi, Ke (Frontiers in Physics, 2020)
A dual-band microstrip patch antenna based on polarization conversion metasurface structure is designed. By etching the complementary split ring resonator (CSRR) on the ground plane, a new resonance frequency is generated. The proposed antenna is obtained through optimizing the structural parameters of CSRR. Compared with the antenna without CSRR, the return loss of the proposed antenna increases by about 40% in the original resonance frequency. The measured results demonstrate good agreement with the simulated ones, verifying the reliability of the antenna. This work provides a way to the design of multi-band antenna.